Prostate Cancer in Male-to-Female Transgender Individuals: Histopathologic Findings and Association With Gender-affirming Hormonal Therapy. (26th December 2022) - Baraban, Ezra; Ding, Chien-Kuang C.; White, Marissa; Vohra, Poonam; Simko, Jeffry; Boyle, Karen; Guo, Charles; Zhang, Miao; Dobs, Adrian; Ketheeswaran, Suvethavarshini; Liang, Fan; Epstein, Jonathan I.
Abstract : Male-to-female (MtF) transgender individuals are at risk for prostate cancer, although guidelines for screening and management in this population are not well established. We describe a series of 9 MtF transgender patients who underwent prostate tissue sampling and highlight histopathologic features and challenges related to pathologic interpretation of prostate tissue in this patient population. Seven of 9 total patients were diagnosed with prostate cancer and all had elevated prostate-specific antigen at the time of diagnosis. Three of the 7 patients diagnosed with prostate cancer had received different types of hormone therapy for gender affirmation before the diagnosis of prostate cancer, and in all 3 of these patients, there was histologic evidence of hormone therapy effect in both benign prostate tissue and/or the adenocarcinoma. The 2 patients with benign prostate tissue underwent transurethral resection for lower urinary tract symptoms and were previously on hormone therapy for gender affirmation. Both of these specimens showed diffuse glandular atrophy and basal cell hyperplasia, indicative of hormone therapy effect on benign prostatic tissue. In the patients diagnosed with prostate cancer, a spectrum of grades was observed, ranging from Grade Group 1 to Grade Group 5. Four patients underwent radical prostatectomy, with 2 cases showing extraprostatic extension and Grade Group 5 prostatic adenocarcinoma, and 2 showing Grade Group 2 prostatic adenocarcinoma. Three of the 4 patients who underwent radical prostatectomy had received gender-affirming hormone therapy before surgery, and all 3 of these specimens showed hormone therapy effect in non-neoplastic prostate tissue and focal hormone therapy effect in prostatic adenocarcinoma. The presence of areas of viable carcinoma without hormone therapy effect enabled the assignment of a Gleason score and Grade Group in these 3 cases. Hormone therapy administered for gender identity affirmation induces histopathologic changes to both benign prostate tissue (nonkeratinizing squamous metaplasia, diffuse atrophy, basal cell hyperplasia, and stromal dominance with decreased numbers of glands) and prostatic adenocarcinoma (nuclear pyknosis, atrophy, cytoplasmic vacuolization, and architectural patterns that would qualify for Gleason 4 and 5 in the absence of hormone therapy effect) that have been traditionally seen in cis-male prostate cancer patients receiving hormone therapy. In the absence of hormone therapy, the morphology of prostatic adenocarcinoma in transgender patients shows classic morphologic features similar to those seen in cis-male patients not on hormone therapy. Prostate cancer with hormone therapy effect may not only be histologically quite subtle and may be overlooked if not suspected, but also should not be assigned a Gleason score because the Gleason score would substantially overstate its biologic potential. Therefore, similar to cis-male patients who have received androgen deprivation therapy for prostate cancer, transgender patients on hormone therapy for gender affirmation may be at risk for both underrecognition and over-grading of prostate cancer, particularly if the pathologist is not aware of the clinical history.